Physical and Psychological Problems in Diabetics (The International Journal for Scientific Research, 2022)
Diabetes is a long-term metabolic illness that has an effect on a person's physical, social, mental, and psychological well-being. Additionally, if left untreated, the psychosocial issues that are most prevalent in diabetes patients frequently have a serious detrimental influence on the patient's well-being and social life. As selfcare for diabetes is the ultimate goal of patient management, addressing such psychosocial components of treatment treatments, including cognitive, emotional, Behavioural, and social factors, would assist overcome the psychological barriers associated with adherence. There is a wealth of knowledge on psychological therapies and self-management strategies for diabetes, but less is known about how psychological reactions and unresolved emotional distresses affect general health. Methodology: The descriptive analytical method was used. Sample: The sample population was considered a group of patients from Al- hospitals.   Results: There is a statistically significant relationship between age and diabetes and the increase in psychological disorders in addition to the relationship between gender and mental disorders, as women are more exposed to psychological problems.
Keywords: Diabetics; Physical Problems; Psychological Problems; Patients